2015
DOI: 10.1007/s00234-015-1574-9
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin-labeling MR imaging of cerebral hemorrhages

Abstract: The use of ASL-MRI is sensitive to the perfusion abnormalities and could thus be helpful to estimate functional abnormalities in cerebral hemorrhage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…Those findings support the concept that a highgrade tumor, with stronger invasiveness and more severe damage to the brain, is more likely to cause CCD. Some studies on other brain diseases also point out that CCD is related to the volume of the lesion [21][22][23]. We further indicated that peritumoral edema should be considered when evaluating the causes of CCD.…”
Section: Discussionmentioning
confidence: 71%
“…Those findings support the concept that a highgrade tumor, with stronger invasiveness and more severe damage to the brain, is more likely to cause CCD. Some studies on other brain diseases also point out that CCD is related to the volume of the lesion [21][22][23]. We further indicated that peritumoral edema should be considered when evaluating the causes of CCD.…”
Section: Discussionmentioning
confidence: 71%
“…After hemispherotomy, section of the perithalamic white matter tracts suppresses seizure expression due to the interruption of the cortical projection bundles to the brainstem and spinal cord and, in the meantime, interrupts the ascending reticular activating system, an essential polysynaptic pathway for arousal through increases of cortical excitability 69 . Crossed‐cerebellar and ipsilateral diaschisis were also recently reported with reduced perfusion of rCBF after thalamic or putaminal hemorrhage 70 . Such significant decreases in neuronal metabolism may be due to reduced neuronal activity secondary to the loss of afferent inputs as in rodents cerebellar interneurons and Purkinje cells decrease their firing rate after inducing focal cerebral ischemia 71 …”
Section: Discussionmentioning
confidence: 96%
“…69 Crossed-cerebellar and ipsilateral diaschisis were also recently reported with reduced perfusion of rCBF after thalamic or putaminal hemorrhage. 70 Such significant decreases in neuronal metabolism may be due to reduced neuronal activity secondary to the loss of afferent inputs as in rodents cerebellar interneurons and Purkinje cells decrease their firing rate after inducing focal cerebral ischemia. 71…”
Section: Neurological Mechanismsmentioning
confidence: 99%
“…[5][6][7][8] Cortical hypoperfusion may also be associated with crossed cerebellar diaschisis (CCD), a depression of CBF and metabolism in the cerebellar hemisphere contralateral to a supratentorial neuronal deactivation. CCD is observed in several disorders that result in neuronal damage or depletion, such as acute ischemic motor stroke, 9,10 hemorrhage, 11,12 and epilepsy with disturbance of the motor network. 13 So far, CCD in migraine has only been described anecdotally 14,15 as posing a risk of subsequent brain infarctions for patients with CCD.…”
mentioning
confidence: 99%